THE INFLUENCE OF CRITICAL PARAMETERS OF BIODIESEL QUALITY ON USE OF BIODIESEL - Sadadinović, J.; Kalfić, A. (Journal of Engineering & Processing Management, 2010)
Biodiesel is a mixture of methyl esters of long chain fatty acids, produced typically by alkalicatalyzed transesterification from vegetable oils. Biodiesel products in the EU must meet EN 14214 quality standard specification. In this specification, values of physical properties and impurities for commercial products are set out, including viscosity, water and sediment, cetane number, CFPP, acid number, glycerol, phosphorus, etc. One of the important parameters, oxidation stability, European standard EN 14214 require a higher level of oxygen stability. Other factors affecting biodiesel quality are environmental conditions, which are mainly the cold flow properties. Biodiesel has a relatively higher CFPP, which limits its application as B100 in low temperature conditions. In addition, biodiesel has a strong tendency to absorb moisture due to its chemical properties.The Objective of this work was to identifications critical parameters of biodiesel quality and their influence on use of biodiesel.